Focus on plastics from land to aquatic ecosystems - van Emmerik, Tim H M (2023)
Plastic pollution in oceans and rivers is of growing concern. Aquatic ecosystems play an important role in transport and storage of plastic waste from land-based storage to riverine and marine environments. This focus issue brings together new insights on the sources, transport dynamics, fate, and impact of plastic pollution through aquatic environments. The work collected in this focus issue shows that urban areas, transportation infrastructure, and wastewater treatment plants are consistently identified as sources for micro-, meso-, and macroplastics. Transport dynamics of plastics over land and through rivers were found to be driven by human factors, flood and storm events, and hydrodynamics, and combinations thereof. Most plastics were found not to make it to the open sea, but rather beach, float in coastal waters, or accumulate on land and within river systems. When exposed to the environment, both conventional and biodegradable plastics degrade into smaller pieces. Yet, the degradation and fragmentation of plastics in the environment remain unresolved. Future work should focus on transferability of new river and region specific insights, collection and exploration of large-scale and novel datasets, source and entry point identification, and understanding fundamental transport mechanisms. This focus issue provides new insights on sources, transport, fate, and impact of plastics, but also emphasizes that need for further work on plastics in aquatic ecosystems.